Association Between Sustained Poverty and Changes in Body Mass Index, 1990–2015: The Coronary Artery Risk Development in Young Adults Study. Issue 6 (13th December 2017) - Elfassy, Tali; Glymour, M Maria; Kershaw, Kiarri N; Carnethon, Mercedes; Llabre, Maria M; Lewis, Cora E; Schneiderman, Neil; Zeki Al Hazzouri, Adina
Abstract: We sought to determine whether sustained poverty is associated with change in body mass index (BMI, calculated as weight (kg)/height (m) 2 ) among 4, 762 black and white adults from the Coronary Artery Risk Development in Young Adults study. Household income in the prior year and current BMI were measured at 7 visits between 1990 and 2015. Sustained poverty was the proportion of visits during which household income was below 200% of the federal poverty level (range, 0%–100%). Sustained poverty and BMI were time-updated. Mean age in 1990 was 30 years. In adjusted linear mixed-effects models, every 10% increase in sustained poverty was significantly associated with faster BMI growth among white men (0.004/year, 95% CI: 0.001, 0.008) and white women (0.003/year, 95% CI: 0.000, 0.006), and slower BMI growth among black men (−0.008/year, 95% CI: −0.010, −0.005) and black women (−0.003/year, 95% CI: −0.006, 0.000). In other words, being always versus never in poverty from 1990 to 2015 was predicted to result in greater BMI gain by 1.00 unit and 0.75 units among white men and women and less BMI gain by 2.0 units and 0.75 units among black men and women, respectively. Sustained poverty was a predictor of changes in BMI with differential associations according to race.